Supplemental selenium source on gut health: insights on fecal microbiome and fermentation products of growing puppies. Issue 11 (12th October 2020) - Pereira, Ana Margarida; Pinna, Carlo; Biagi, Giacomo; Stefanelli, Claudio; Maia, Margarida R G; Matos, Elisabete; Segundo, Marcela A; Fonseca, António J M; Cabrita, Ana Rita J
ABSTRACT: Selenium is an essential trace element that can modulate the gut microbiome with an impact on host health. The present study aimed to evaluate the effects of organic (selenium-enriched yeast) vs inorganic (sodium selenite) selenium source on fecal end-fermentation products and gut microbiome of puppies from 20 to 52 weeks of age. Alpha and beta diversity of the gut bacterial community were affected by age but not by gender or selenium source. The relative abundance of taxa was differently affected by age, and the DNA concentration of all selected bacterial groups increased with age, although total volatile fatty acids (VFA), acetate, propionate, caproate and lactate concentrations decreased. Organic selenium was associated with a higher concentration of total VFA, propionate and butyrate, a higher number of DNA copies of Lactobacillus, and a trend to lower DNA copies of Escherichia coli . Effects on fecal microbiome during growth differed with selenium source. Females had higher fecal end-fermentation products related to protein degradation, whereas males had higher DNA concentration of Bifidobacterium . Organic selenium might be beneficial over inorganic for dog food supplementation due to the positive modulation of the gut microbiome observed in puppies. Abstract : Supplementation of dog food with organic selenium over inorganic selenium positively modulated the gut microbiome of growing puppies which might contribute to gut health.